Pengaruh Kecukupan Modal, Struktur Modal dan Ukuran Perusahaan Pada Profitabilitas Dengan Risiko Kredit Sebagai Pemoderasi - Purba, Aurelia Gracella; Damayanthi, I Gst. Ayu Eka (E-Jurnal Akuntansi; Vol 23 No 2 (2018), 2018)
Banking play s an important role in economic development. Bank has a n objective to obtain profitability. Profitability is an indicator to measure the performance of bank. Return On Assets  is a proxy to measure the ability of management in obtaining profit through total assets owned. This study aims to examine the effect of capital adequacy, capital structure, and firm size on profitability with credit risk as a moderating variable. This study uses non-probability sampling method with purposive sampling technique in banking sector in Indonesia Stock Exchange period 2012-2016. The number of samples is 130. T he analysis technique used is Moderated Regression Analysis. The results show capital adequacy and capital structure does not affect the profitability and firm size positively affects the profitability. C redit risk is not able to moderate the influence of capital adequacy and capital structure on profitability and credit risk negatively moderate s the effect of firm size on profitability .